Photoshop Sdn. Bhd. / Ismail Yusop ... [et al.] - Yusop, Ismail; Alwi, Hakim Akmal; Mohd Bakri, Ahmad Afzan; Abdullah, Ahmad Syamil; Abd Rahman, Mohammad Ikram (Faculty of Mechanical Engineering, 2003)
PhotoShop Sdn Bhd is a business formed by 5 business partners that inspire to be successful entrepreneurs. PhotoShop Sdn Bhd is involves in indoor and outdoor photography services and retail selling of photographic equipments, hand phone reload card and photostat services. FujiFilm Sdn Bhd is our sale distributor for our shop. Our target market is the resident of Bandar Baru Sri Petahng, the students and also the teenagers who seek up the latest technology of photographic. For that, we sell digital cameras and provide service to guide how to use it. Furthermore, we provide service in video recording in different kinds of ceremony. As this business not yet preferable in this area, we assure this business can be profitable. Our business will stand operation on 1st December 2003. It is situated at 10, Jalan Raden Amim, Bandar Baru Sri Petaling 57000 Kuala Lumpur. We choose this location because there is only few photos shop in this area. Besides, we're confident that we can make profit here as there are many families, students, workers and also teenagers that influence to try new technology. Furthermore the purchasing power of the community here is increased and ready to be our customer.